'The link between practices of Human Resource Management and Supply Chain Management' - Kouali, Marianthi (2013)
The scope of this study is to establish the significance of human resource practices in reaching high levels of supply chain management performance through the comparison of two companies that belong in the telecommunications industry in the Republic of Cyprus. For the purposes of this study, a literature review was undertaken which was divided in three parts. The first part includes aspects related to Supply Chain Management, the second part includes the best practice of Human Resource Management and finally the third part explains the research that has already been carried out in combining the two disciplines. Moreover, this study uses a quantitative method of research to gather primary data. A questionnaire was given to a sample of employees in the two companies which examined the development of human resource practices such as recruitment, training and development, compensation and employment security. The answers of the respondents were analysed using the Statistical Package for Social Sciences (SPSS). In order to compare the human resource practices and state whether they have a significant impact in the performance of the two organizations the use of Mann-Whitney U test was considered appropriate. The findings of the study revealed that training and compensations on performance are significantly different between the two organizations. Also, by comparing the performance measurements of the two companies, this study identified that the human capital of an organization as well as training and rewards have an impact on the supply chain performance. However, this research is only a pilot study and therefore further studies need to be carried out to test the validity of the results.